Verbos de movimento que lexicalizam modo e trajetória - Benck, Suelen (2020)
This research aims at investigating the linguistic behavior of verbs of movement that lexicalize mode and path in Brazilian Portuguese (Pt-Br). The review of literature on lexical semantics has assumed that the mode of movement and path are elements of semantic structure in terms of their complementary distribution, and therefore, these verbs cannot be lexicalized in the same lexical root. Despite the theoretical framework used, this investigation is circumscribed to a subclass of verbs of movement that lexicalize mode and path loaded into the same verb root as a means to reformulate the concept of complementary distribution of the given properties which are mode and path. Initially, we narrowed down this subclass to at least 72 verbs, and once we defined which verbs to analyze, we described the linguistic behavior of the verb subclasses in Pt-Br. Afterwards, we develop and applied equivalence and redundancy tests in order to verify the double lexicalization of semantic properties of the set of verbs. We verified the checking tests of adversative value and specification by path adjunction are likely to demonstrate how sentence reformulation cause semantic loss or semantic addition by highlighting which information was lost or added to the sentence context. Furthermore, the tests that checked the anaphoric contradiction and restatement of a given mode highlight that adjuncts express the same mode value and are likely to be redundant in a sentence and that they can retrieve information by means of anaphor. The investigation has enabled us to evidence that there is a number of verbs of movement that lexicalize mode and path in Pt-Br, and that these verbs present a semantic behavior that is easy to demonstrate by means of redundancy and equivalence tests. In the light of these findings, we conclude that there is a subclass of movement verbs that lexicalize mode and path and that they do not present a verifiable restriction regarding semantic load in terms of mode and path.